IMPLEMENTATION OF COMPETENCY-BASED HUMAN RESOURCE MANAGEMENT TO IMPROVE ORGANISATIONAL EFFECTIVENESS AT SERVICE COMPANIES IN INDONESIA - Khaeruman, Khaeruman; Dewi, Irma Nirmala; Fatari, Fatari; Sain, Zohaib Hassan (Yayasan Education and Social Center, 2026)
This study aims to analyse the application of competency-based human resource management in improving organisational effectiveness in service companies in Indonesia. The research approach used is a descriptive qualitative approach, with data collected through in-depth interviews, non-participant observation, and documentation. The research was conducted in November 2025 and involved purposively selected informants, including organisational leaders, human resource managers, supervisors, and employees. Data analysis was conducted thematically using NVivo software to identify patterns, categories, and central themes related to competency management and organisational effectiveness. The results showed that implementing competency-based HRM significantly improved organisational effectiveness, particularly through precise competency mapping, integrating competencies into recruitment, training, and performance appraisal processes, and increasing productivity and service quality. The findings also revealed that the successful implementation of competency-based HRM was greatly influenced by management commitment and organisational policy support. This research makes theoretical contributions to the development of human resource management studies and practical contributions to service companies by helping them design competency-oriented HR management strategies to improve organisational effectiveness sustainably.